Human parainfluenza virus surveillance in pediatric patients with lower respiratory tract infections: a special view of parainfluenza type 4 - Luciano M. Thomazelli; Danielle B. L. de Oliveira; Giuliana S. Durigon; Brett Whitaker; Shifaq Kamili; Eitan N. Berezin; Edison L. Durigon (Elsevier, 2018)
Objective: Characterize the role of human parainfluenza virus and its clinical features in Brazilian children under 2 years of age presenting with acute lower respiratory tract infections. Methods: Real-time assays were used to identify strains of human parainfluenza virus and other common respiratory viruses in nasopharyngeal aspirates. One thousand and two children presenting with acute lower respiratory tract illnesses were enrolled from February 2008 to August 2010. Results: One hundred and four (10.4%) patients were human parainfluenza virus positive, of whom 60 (57.7%) were positive for human parainfluenza virus-3, 30 (28.8%) for human parainfluenza virus-4, 12 (11.5%) for human parainfluenza virus-1, and two (1.9%) for human parainfluenza virus-2. Seven (6.7%) patients had more than one strain of human parainfluenza virus detected. The most frequent symptoms were tachypnea and cough, similar to other viral respiratory infections. Clinical manifestations did not differ significantly between human parainfluenza virus-1, -2, -3, and -4 infections. Human parainfluenza virus-1, -3, and -4 were present in the population studied throughout the three years of surveillance, with human parainfluenza virus-3 being the predominant type identified in the first two years. Conclusion: Human parainfluenza viruses contribute substantially to pediatric acute respiratory illness (ARI) in Brazil, with nearly 30% of this contribution attributable to human parainfluenza virus-4. Resumo: Objetivo: Caracterizar o papel do VPH-4 e suas características clínicas em crianças brasileiras com menos de dois anos de idade com infecções agudas do trato respiratório inferior. Métodos: Ensaios em tempo real foram utilizados para identificar tipos de VPH e outros vírus respiratórios comuns em aspirados nasofaríngeos. Mil e duas crianças com doença aguda do trato respiratório inferior foram inscritas para participar de fevereiro de 2008 a agosto de 2010. Resultados: 104 (10,4%) pacientes eram VPH positivos, dos quais 60 (57,7%) eram positivos para VPH-3, 30 (28,8%) para VPH-4, 12 (11,5%) para VPH-1 e dois (1,9%) para VPH-2. Sete (6,7%) pacientes apresentaram mais de um tipo de VPH detectado. Os sintomas mais frequentes foram tosse e taquipneia, semelhantes a outras infecções respiratórias virais. As manifestações clínicas não diferiram de forma significativa entre as infecções por VPH-1, -2, -3 e -4. Os VPH-1, -3 e -4 estavam presentes na população estudada ao longo dos três anos de vigilância, e o VPH-3 foi o tipo predominante identificado nos primeiros dois anos. Conclusão: Os VPHs contribuem substancialmente para a DRA pediátrica no Brasil com quase 30% dessa contribuição atribuível ao VPH-4. Keywords: Human parainfluenza virus, Respiratory virus, Pediatric patients, Acute respiratory illness, Human respirovirus 4, Palavras-chave: Vírus da parainfluenza humana, Vírus respiratório, Pacientes pediátricos, Doença respiratória aguda, Respirovírus humano 4